The Zero-Sum Mindset and Efforts to Defund ALA - Andrew Thomas Sulavik (The Political Librarian, 2023)
This editorial summarizes a county meeting, where a vote was taken to defund the county public library system’s institutional membership to the American Library Association (ALA) and the zero-sum thinking that supported it. It is a scenario that is repeatedly playing out throughout the country at both state and local levels. The rationale behind it needs to be understood before steps to curtail it can be taken.